Development Of Interactive Learning Media Based On The Google Sites Website Assisted With Wordwall On Logarithm Material - Zahroatul Fitroh; Zainullah Zuhri (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to develop website-based interactive learning media with the help of a wordwall on logarithm material. The research method uses Research and Development (R&D) with the ADDIE development model with stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research trial involved 40 class X students of Al-Yasini Superior High School, school teachers, and lecturers in the Mathematics Education Study Program Nahdlatul Ulama’ University. Data collection techniques in this research are interviews and learning media assessment questionnaires. Next, the data was analyzed using a Likert measurement scale. The research results show that the media: (1) Website-based interactive learning media assisted by wordwall on logarithm material is said to be valid by media experts with a percentage of 92%, and material experts 95%; (2) learning media is said to be practical by small group students with a percentage of 84% and large group students with a percentage of 77%; (3) learning media is said to be effective based on the results of the game scores obtained by large group students with scores that reach the minimum completeness criteria of 75 in mathematics subjects. From these 3 conclusions, it can be said that the media has been assessed with a good predicate and can be used in related material by teachers.